Sensors for optical thermometry based on luminescence from layered YVO(4): Ln(3+) (Ln = Nd, Sm, Eu, Dy, Ho, Er, Tm, Yb) thin films made by atomic layer deposition - Getz, Michael N. (Sci Rep, 2019)
Below the Earth’s crust, temperatures may reach beyond 600 K, impeding the batteries used to power conventional thermometers. Fluorescence intensity ratio based temperature probes can be used with optical fibers that can withstand these conditions. However, the probes tend to exhibit narrow operating ranges and poor sensitivity above 400 K. In this study, we have investigated single and dual layered YVO(4): Ln(3+) (Ln = Nd, Sm, Eu, Dy, Ho, Er, Tm, Yb) thin films (100–150 nm) for use in fluorescence intensity ratio based temperature sensors in the 300–850 K range. The type of lanthanide emission can be fine-tuned by adjusting the thickness of each layer, and the layered structure allows for emission from otherwise incompatible lanthanide pairs. This novel multi-layered approach enables high sensitivity over a broad temperature range. The highest relative sensitivity was achieved for a dual layered YVO(4): Eu(3+)/YVO(4): Dy(3+) sample, exhibiting a maximum sensitivity of 3.6% K(−1) at 640 K. The films were successfully deposited on all tested substrates (silicon, iron, aluminum, glass, quartz, and steel), and can be applied homogenously to most surfaces without the use of binders. The films are unaffected by water, enabling non-contact temperature sensing in water, where IR thermometers are not an option.